The role of nitric oxide on the oxytocin induce analgesia in mice - Abbasnezhad, Abbasali (Iran J Basic Med Sci, 2016)
OBJECTIVE(S): Analgesic effects of oxytocin and it's the other physiological effects were well-known. The aim of present study was determination of nitric oxide role on analgesic effects of oxytocin in mice. MATERIALS AND METHODS: 216 male Albino mice were divided randomly into two experimental groups, tail flick and formalin test. Each experimental group consists of three main groups including: saline, L-arginine (50 mg/kg) and L-NAME (10 mg/kg) intraperitoneal (IP) injection. 15 min after injection in each of the following groups, the animals in each groups divided to the three subgroups including: saline (n=12), oxytocin (1 mg/kg) (n=12) and oxytocin (1 mg/kg) + atosiban (1 mg/kg) (n=12) was injected IP and then after 30 min of use the formalin test and tail flick were to evaluate the response to pain. RESULTS: Area under the curve (AUC) in the late phase of the formalin test, in sub-groups oxytocin + saline and L-NAME were significantly decreased compared with saline + saline group (P<0.05 to P< 0.001), and AUC in L-arginine + saline and atosiban + saline + oxytocin were significantly increased compared with oxytocin + saline group (P<0.05). Tail flick tests as well as a significant reduction in the AUC in oxytocin + L-arginine and atosiban + saline + oxytocin groups were compared with Oxytocin + Saline group (P<0.001). CONCLUSION: Oxytocin has analgesic effects in the acute and late phase of pain in the formalin test. Moreover, exogenous increasing of nitric oxide reduced the analgesic effect of oxytocin.